In Situ Probing Citrullinated Sites in a Peptide by Reactive Desorption Electrospray Ionization Mass Spectrometry. (1st December 2017) - Shin, Eunbi; Cha, Sangwon
Abstract : Citrullination is a post‐translational modification that converts arginine into citrulline through deimination. As citrullination is accompanied by only about 1 Da increase in mass, ion signals of a citrullinated peptide in a mass spectrum are always overlapped with the isotope peaks of its control (a noncitrullinated form). Therefore, off‐line, covalent labeling techniques on citrulline residues were usually employed to investigate citrullinated sites by mass spectrometry (MS). Recently, reactive desorption electrospray ionization (reactive DESI) MS was introduced as a tool for selective, in situ modification of target analytes. In reactive DESI MS, a chemical reagent that can readily react with a target analyte is sprayed onto a sample spot and resulting products are analyzed by MS. Here, we developed a reactive DESI MS method for determining the citrullinated sites in peptides by employing phenylglyoxal as a derivatization agent, and succeeded in selectively modifying a citrulline residue in a peptide. Abstract :